Geological Analysis for Slope Stability Using the Rock Structure Rating (RSR) Method and Atterberg Limit at Riau - West Sumatra Cross road Km 165 Harau Subdistrict, Lima puluh Kota Regency, West Sumatra Province - Husnul Kausarian; Shaury Aldila; Batara; Dewandra Bagus Eka Putra; Fitri Mairizki (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
Stability on the slope was considered important for the safety of people who pass through the highway. Failure of slopes on highways can cause losses especially roads had an important role in community activities. The research was located on the Riau – West Sumatra Km 165. The purpose of this research was to find out treatment or mitigation that can be given to the research slope and know the soil classification based on the analysis Atterberg Limit. The research slope was divided into 3 parts using analytical Rock Structure Rating (RSR) method based on different slope conditions. And 1 part of the slope has become soil using the analytical method Atterberg Limit. Treatment or mitigation that can be given to the research slope, namely the use of rock shopandshotcrete based on the RSR diagram and the use of rock embankments to resist landslides.